THE OPTIMAL RATIO OF NILE TILAPIA (Oreochromis niloticus) AND COMMON CARP (Cyprinus carpio) FOR IMPROVING PRODUCTIVITY ON DEEP WATER POND - Imam Taufik; Sutrisno Sutrisno; Eri Setiadi (Indonesian Aquaculture Journal, 2013)
Pond productivity can be increased by applied polyculture system in the deep pond. The purpose of this experiment is to examine the optimal ratio between nile tilapia and common carp, in order to increase the productivity. Nine concrete tanks (15 m2) with water depth of 2.2 m and were completed by water inlet, water outlet, and aeration. Both of nile tilapia and common carp with size ranging of 5-8 cm in total length were used. Stock density was 150 ind./m2. The difference ratio of both fish tilapia and carp of fish stocked as a treatment. The fish ratio this experiment were as followed: A) 100%; B) 80%:20%; C) 60%:40%. Fish fed by pellet until at ad libitum. The duration of experiment was 100 days. Parameters such as survival, growth, and productivity were observed every ten days during the experiment period. Water quality parameters were also periodically observed. The results showed that survival of nile tilapia among the treatments were not significantly different (P>0.05) where survival of common carp at B treatment was better than C treatment (P<0.05). The highest of growth of absolute weight (94.86±2.85 g) and total length (14.71±1 cm) of nile tilapia at B treatment was found (P<0.05) where the best of growth of absolute weight (106.52±10.47 g) and total length (11.57±1.78 cm) of common carp was also found at B treatment (P<0.05). Biomass productivity at B treatment was the highest compared with A treatment (P<0.05). Combination between polyculture and the deep water pond technology could increase productivity. The polyculture system and the deep water pond technology would be able to keep constant water quality within in the threshold accordance with the regulation for fish culture.